Financial Literacy as a Driver of Governance and Sustainability in Small and Medium Enterprises - Kaur, Manpreet; Dhiman, Babli (Prabandhan: Indian Journal of Management, 2025)
Purpose : The research was conducted to determine how governance systems and financial resources affected sustainability, with a particular focus on the importance of financial literacy (FL) among owners of small and medium-sized enterprises (SMEs). Design/Methodology : The questionnaires were used to gather data, and a convenience sample of small and medium-sized business owners in Punjab was utilized. Based on 308 valid answers, the research applied the partial least squares-structural equation modeling (PLS-SEM) method to analyze the correlation between the variables. Results : The results showed that FL significantly affected access to loans and other financial resources, enabling sustainability to a large extent. The statistical significance of the correlation between FL and sustainability governance was not high. The findings revealed that SME owners who became more financially literate were in a better position to access external funding, which enabled them to manage their businesses in a more sustainable manner. Practical Implications : SME owners, managers, and universities need to cooperate more closely to enhance education and assist individuals in making more informed decisions. The research identified various limitations and recommended that another study be conducted on how inequalities in literacy levels, resource availability, and entrepreneurial lifestyles affected sustainability. Novelty : The research clarified the role of entrepreneurial FL as a factor in accessing external financing and what makes a successful entry into the regulatory platform and its viability.